Immunohistochemical changes of maxillary sinus mucosa with underlying adenomatous polyposis - Yu. M. Andreychyn; I. S. Kovalenko (Patologìâ)
In maxillary sinusitis pathogenesis researchers paid much attention to the role of paranasal sinuses, sinus drainage dysfunctions, mucocyliary transport system disorders in cases of damage of sinuses mucous membranes. Pathohistological, immunohistochemical and morphometric studies of mucosa were conducted. However, to evaluate the local inflammatory response in cases of chronic sinusitis and improvement of individual therapy for the patients, the immunohistochemical studies of the composition of inflammatory immunocyte infiltrates of paranasal sinus mucosa and adenoid vegetations bioptate would be reasonable.